The impact of organisational downsizing on survivor employees’ safety and health: a case of Zimasco Kwekwe (pvt) limited - Marandure, Tsvakai Jonny (Midlands State University, 2018)
Organisational downsizing is a strategy employed by most limping organizations in quest for survival. The strategy can have fatal effects if not properly implemented. The study evaluated organizational downsizing and its subsequent effects to the remaining employees’ safety and health focusing on Zimasco Kwekwe. This was driven by the premise that organizations must ensure uptight safety and health systems are in place regardless of challenges faced as this cannot be compromised. Qualitative research approach was used to obtain several truths of the study. It focused on real life experiences of the respondents which assisted in bringing to the fore the experiences of the participants. Thus, the study used descriptive approaches to obtain truth which are the hermeneutics and case study designs which assisted in coming up with inferences within a natural setting. This also assisted in ascertaining the impacts of downsizing on survivor employee’s safety and health. The study population was 532 giving a sample of 53 respondents obtained through stratified random sampling. Systematic random sampling was then used to afford respondents equal selection opportunity. The study then purposively identified and interviewed two (2) Safety, Health and Environmental practitioners from the managerial strata with a view to have an inclusive and generalizable finding. Content and thematic analysis methods were used to analyse data gathered through documentary sources and interviews respectively. The research found that, Zimasco recorded the worst safety and health performance during the period 2013/2014 compared to the period 2010 to 2012. This was noted through respondents’ sentiments that there were a lot of inconsistencies in the safety and health performance during this period. To note was a fatality recorded in December 2013 and an increase of disabling injuries from the average and budgeted 1 incident/ year to 5 in 2013 and 9 in 2014. The SHE surveillance audit was last conducted in 2014 and a 4-star rating was recorded against the usual 5 star for prior years. This was mainly attributed to the 2013 fatality and the recorded disabling injuries that reflected deterioration of systems and standards. The major identified causes of these accidents were skills gaps, training gaps, role overload and fear of the unknown which are all an outcome of skills displacement post the downsizing process as the rightly skilled employees were terminated. Those left remained with huge demands making it difficult to comply with all safety requirements and at times unknowingly breaching standards which compromised their safety and health. Such actions were also driven by health effects experienced mainly depression, psychological trauma, fatigue and distress. The effects began to be most visible post the downsizing process. Sickness absence rate also picked from 2013 with a few labour complement compared to prior years. Though the sickness absence record was high in 2012, this was mainly due to the huge complement. In terms of percentage occurrence of sickness absence cases, the 2013/2014 record was high. The study established that downsizing has got effects on employee safety and health if no attention is paid to people related issues whilst undertaking the process as it results in negative health effects on survivor employees as well as increased accidents. The study therefore concluded that organizations need to embrace organizational downsizing as a holistic package that does not neglect and compromise on the safety and health of the survivor employees.